FRI0361 Aortic aneurysm related to gca – an overestimated risk?. (23rd January 2014) - Hafner, F.; Haas, E.; Dejaco, C.; Gary, T.; Froehlich, H.; Szolar, D.; Thonhofer, R.; Brodmann, M.
Abstract : Background: Giant cell arteritis (GCA) is an autoimmune disorder affecting medium- and large sized arteries. The most common symptoms are related to ischemic cranial involvement. Nevertheless, asymptomatic aortic involvement may cause aneurysm and dissections[1 ]. Several studies in this issue had limitations regarding imaging methods and matched control groups. Objectives: To evaluate aortic diameters in a cohort of GCA patients and a matched control group by CT-angiography (CTA) as a uniform imaging method. Furthermore, to detect the prevalence of aortic aneurysms, defined as an aortic diameter >50mm or local widening >50%, and a body surface area (BSA) adjusted aortic diameter above the 95 th percentile. Methods: All patients with diagnosed GCA at least two years prior to enrolment underwent CTA of the thoracal and abdominal aorta. Patients without a rheumatic disease, who underwent thoracal and abdominal CT for other reasons (i.e. infection, cancer) participated in the age matched control group. A quotient of aortic diameters and BSA was calculated [2 ]. The study was approved by the local ethics committee, written informed consent was obtained. Results: 128 Patients with GCA (99 female) and 111 subjects of the control group were included. Mean age of GCA patients was 74.0 ± 7.8 years, included 73 ± 117 months after GCA diagnosis. Mean thoracic aortic diameters [values/m² BSA] were 34.66 ± 4.59mm [19.89 ± 3.02mm/m²], 28.20 ± 3.50mm [16.17 ± 2.30mm/m² BSA] and 25.83 ± 3.17mm [14.82 ± 2.21mm/m² BSA] at the ascending aorta (AAT), the aortic arch (ART) and the descending aorta (DAT) respectively. The AAT diameter did not differ between GCA and control group subjects with a mean value of 34.42 ± 4.31mm [19.58 ± 2.80mm/m² BSA, p=0.411]. The mean diameters of the ART and the DAT differed significantly compared to GCA patients with values of 27.33 ± 2.86mm [15.56 ± 2.12mm/m² BSA, p=0.036] and 24.77 ± 2.70mm [14.09 ± 1.83mm/m² BSA, p=0.006]. Aortic aneurysms, defined as aortic diameter >50mm were present in 1 patient of the GCA group (0.8%) and 1 in the control group (0.9%, n.s.). Five patients of the GCA group (3.9%) and 6 control group subjects (5.4%, p=0.759) had a BSA adjusted diameter of the DAT above the 95 th percentile as proposed by Kälsch et al.[2 ]. We did not observe any aortic dissection or an aneurysm of the abdominal aorta. Mean abdominal aortic diameter did not differ between GCA and control group subjects with values of 21.0 ± 2.5mm and 21.0 ± 2.3mm respectively (p=1.00). Conclusions: Vigilance and screening for aortic aneurysms is considered in GCA patients; however, our data of a uniform vascular imaging in GCA patients and an age matched control group suggest that the risk developing aortic aneurysms after GCA diagnosis might be overestimated. Uniform imaging methods and adjustment for BSA would be essential when considering aortic studies in GCA. References: Mackie SL, Hensor EM, Morgan AW, Pease CT. Should I send my patient with previous giant cell arteritis for imaging of the thoracic aorta? A systematic literature review and meta-analysis. Ann Rheum Dis. 2012 Dec 22. Kälsch H, Lehmann N, Möhlenkamp S et al. Body-surface adjusted aortic reference diameters for improved identification of patients with thoracic aortic aneurysms. Int J Cardiol. 2013 Feb 10;163(1):72-8 Disclosure of Interest : None Declared